INTEGRATED GEOPHYSICAL METHOD FOR GOLD EXPLORATION IN BIRNIN GWARI, KADUNA STATE NIGERIA - Alaba, Olanrewaju C.; Gbolagade, Musiliu Adebanji; Akinbinu, Victor Abioye (FUDMA JOURNAL OF SCIENCES, 2025)
Birin Gwari is well recognised for having a wealth of minerals, particularly gold deposits, but its exploration efforts based on the use of single method have resulted to inaccurate results when it comes to detecting mineralisation zones and target accuracy. This problem was addressed by combining induced polarisation (IP) and electrical resistivity imaging (ERI) surveys techniques to further investigate the interpreted aeromagnetic data of the study. This combined technique improved subsurface characterization of the identified gold-mineralized zones with detail geological information. The study adopted GDD IP and electrical resistivity imaging survey equipment to probe further the selected nine IP profiles of delineated anomalous from the aeromagnetic survey. The results from the 2-D inverted IP - resistivity models revealed that 30 out of 34 of the anomalous zone with high chargeability and high to average resistivity were identified. Also, 33 of the IP profiles were highly charged, and their chargeability increased with depth. Meanwhile, 29 of the delineated anomalous has a width length less than 10 m while 5 has greater than 10 m. However, the depth to top length of the 34 anomalies varied from 5 to 81 m. Therefore, the study came to the conclusion that the geophysical parameters of each of the identified anomalous and the maps of mineral prospective priority targets should be served as a reference for core drilling of the suggested anomalous points.